A case study on using instructor-recorded videos in an upper level economics course. (September 2016) - Gulley, O. David; Jackson, Aaron L.
Abstract: We adopted a version of the flipped classroom concept, defined as delivering some course material via short video lectures to be watched in advance of attending class, for an upper-level undergraduate economics course. Using a survey administered to both flipped and non-flipped sections of the course, we find modest evidence of either short term or long term benefits to students in terms of improving understanding of course material, effective use of time in class, and retention of course material.